PERLINDUNGAN HUKUM DANA NASABAH DALAM EKOSISTEM DIGITAL WALLET HASIL INTEGRASI PERBANKAN DAN FINTECH DI INDONESIA - Opik Sepriadi; Hasnah Aziz; Salman Al Ghifari; Unggul Budi; Ridwan (CV. Lafadz Jaya, 2026)
The development of financial technology and digital transformation in the banking sector has led to the integration of digital wallet services as part of the modern payment system in Indonesia. This integration provides convenience, efficiency, and financial inclusion for society. However, the increasing use of digital wallets also raises various legal risks, particularly concerning customer fund protection, digital transaction security, personal data leakage, account misuse, and weak accountability mechanisms in the event of consumer losses. This study aims to analyze the legal protection of customer funds within the digital wallet ecosystem resulting from the integration of banking and fintech services in Indonesia, including an analysis of electronic contracts and digital transaction security based on Indonesian positive law. The research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that legal protection for customer funds has been regulated through various laws and regulations, including Consumer Protection Law, Electronic Information and Transactions Law, Personal Data Protection Law, as well as regulations issued by Bank Indonesia and the Financial Services Authority. Nevertheless, these regulations still face challenges such as regulatory disharmony, weak supervision of fintech companies, and low digital literacy among the public. Therefore, regulatory harmonization, strengthened cybersecurity systems, enhanced regulatory supervision, and stronger accountability of digital financial service providers are necessary to ensure legal certainty and optimal protection for customer funds.